Control of gas pipeline leakage detection based on hybrid inline fiber interferometer - Nada F. Noori; Tahreer S. Mansour (Institute of Advanced Engineering and Science, 2023)
Hybrid inline fiber interferometers gained attention recently especially in the building control and detection fields due to their hybrid multi-path interferences, multi-parameter measurements, high sensitivity, and high precision. This work used etched multimode fiber (MMF) to introduce a novel medical gas pipeline leakage detector based on hybrid Fabry-Perot/Mach-Zehnder inline fiber interferometer (FP-MZI). The hybrid FP-MZI of this work consisted of two cascaded identical fiber Bragg gratings (FBGs) spliced to coreless fiber sandwiching the MMF. Four samples of different MMF lengths and sizes were used as sensing heads in the detection measurements. Self-imaging and phase-equations of the proposed interferometer were solved analytically to select the required length; then COMSOL software was used to ensure the occurrence of the required interference along the proposed interferometer at the designed wavelength. Two medical gas sources; air compressor and high-pressure gas cylinder, attached to two pipelines of size 15×0.7, and 12×0.6 mm was used to provide the required pressure. Gas leak was introduced to the pipes manually through controlled valves and measured using the proposed hybrid FP-MZI. Both constant and variable gas flowrates was investigated with variable gas pressures. The obtained sensitivity was ranged from 0.17-20.9 pm/bar for all of the investigated cases.